Gate interface engineering for subvolt metal oxide transistor fabrication by using ion-conducting dielectric with Mn2O3 gate interface - Pal N.; Sharma A.; Acharya V.; Chourasia N.K.; Biring S.; Pal B.N. (My University, 2025)
A solution-processed high-performance subvolt (<1 V) tin oxide (SnO2) thin film transistor (TFT) has been fabricated onto an ion-conducting Li−Al2O3 gate dielectric by utilizing a high-permittivity Mn2O3 gate interface. A comparative device characterization of two different TFTs with and without a Mn2O3 gate interface with an ionic dielectric ensures that n-type Mn2O3 induces an additional electron to the semiconductor/dielectric interface trap states. Consequently, the TFT with a Mn2O3 interface achieves a lower subthreshold swing (SS) by keeping the threshold voltage closer to zero compared to the TFT without the Mn2O3 gate interface. This SnO2 TFT with Mn2O3 interface requires only 0.6 V to saturate the drain current, and device performance under such low-voltage (0.6 V) operation exhibits an electron mobility of 17 cm2/V·s with on/off ratio of 3.3 × 104 and subthreshold swing of 124 mV/dec. This work provides a potential approach to achieve a high-performance low-voltage TFT by selecting a suitable combination of dielectric materials. © 2019 American Chemical Society